PERBANDINGAN EFEK PERASAN LIDAH BUAYA (Aloe vera) DENGAN POVIDONE IODINE TERHADAP KADAR SUPEROXID DISMUTASE DAN MALONDIALDEHID SERUM TIKUS WISTAR DENGAN LUKA SAYAT - Ilham Rial Ali; Rosaria Dian Lestari; Diah Andriana (Jurnal Kedokteran Komunitas, 2020)
Introduction: Aloe vera has an antioxidant effect that can prevent the increasing of human free radicals caused by injury that can increase free radicals while povidone iodine can accelerate wound healing. This study was conducted to compare the use of Aloe vera juice and povidone iodine in reducing oxidative stress responses in terms of serum SOD and MDA levels in wistar rat serum with incision wounds.Method: Experimental animals (n = 24, male wistar rats aged 2-3 months) were divided into PB groups (povidone iodine) and treatment groups that were given Aloe vera juice with a concentration of 20% (KP1), 40% (KP2) and 80% (KP3) at a dose of 0.5 g / rat / day topically for 6 days. Rats were incised 2 cm long with a depth of 0.2 cm on the back with a scalpel. Serum SOD and MDA levels were measured by spectrophotometry. The data obtained were analyzed using SPSS version 17 with a significant p <0.05Result: According to Mann Whitney test, there were significant decreases in serum SOD levels in the KP1 group (419.67 ± 23.97, p0.004), KP2 (450.96 ± 36.57, p0.004) and KP3 (465.59 ± 29, 49, p0.004) compared with PB (582.63 ± 57.20). Calculations using One Way ANNOVA showed a significant decrease in serum MDA levels in the KP1 group (25.48 ± 0.81, p0.027), KP2 (25.31 ± 1.83, p0.015) and KP3 (22.69 ± 0.77, p0.000) when compared with the administration of povidone iodine (27.11 ± 0.98).Conclusion: Aloe vera juice with a concentration of 20% (KP1), 40% (KP2) and 80% (KP3) can significantly increase serum SOD levels and significantly reduce serum MDA levels better than povidone iodineKeywords: Incision Wound, Oksidatif Stress, Aloe vera, Free Radical